THE TEACHERS STRATEGIES IN OVERCOMING STUDENTS DIFFICULTIES IN WRITING DESCRIPTIVE TEXT - Ida Farida, - (2011)
English as a foreign language in Indonesia plays a vital role. Based on this need, the government tries to place English as the primary foreign language taught at elementary schools to tertiary level in Indonesia. Currently, the results of English teaching in Indonesia are still low. To respond to the low quality of English teaching in schools, the teachers and language practitioners behave to design interesting method, materials, and approach to be employed in the classroom setting. One of authentic materials employed in the classroom is Problem-based learning. The present research entitled The Use of Problem-Based Learning in Developing Students' Speaking Ability was to investigate whether PBL was effective in developing students' speaking ability. It was also aimed at finding out students' responses toward the use of PBL in developing student's speaking ability. The research was conducted at one vocational school in Cimahi. The research employed a quasi-experimental method. Speaking pre-test, post-test and questionnaire were employed to obtain the data. The data were analyzed using independent t-test to see whether or not the means of the two groups are significantly different The statistical computation showed that Problem-based learning was effective in improving students' speaking ability (post-test scores of experimental group, M = 19.8400, was considered there is likely different from the scores of control group, M= 17.7200). This study also reveals that the Problem-based learning can motivate students to learn, thus, students' achievement and understanding the materials were improved. In addition, teacher can create meaningful class by encouraging students to be autonomous learner and providing students with real life problems which will not merely develop student's critical thinking ability but also it will be beneficial for their future learning and career (life-long learning). The appropriate design of learning objectives which considers students' needs and language level may ease teachers to utilize Problem-based learning in developing students' speaking ability. The teachers may try to take advantages of Problem-based learning to be used in their classroom activities.